National stock assessment program : the Philippine capture fisheries atlas. (Philippines : The Philippine Journal of Fisheries, 2017)
A survey of recreational fishing and fish stocks in the United States, based on the Magnuson-Stevens Fishery Conservation and Management Act of 2006